Enhanced Power aware Multipath Routing Protocol for MANETs - .K.J, Shimja; George, Joish (IJRDO -Journal of Computer Science Engineering, 2015)
The tremendous developments in wireless technology made Mobile Ad hoc Networks(MANETs)inevitable in our day to day life.MANET is a set of mobile nodes or devices with dynamically varyingtopology which does depend on any pre-existing infrastrure.These mobile nodes are run by batteries withlimited capacity. Power failure of nodes and unnecessary energy consumption are the critical issues in energyefficient routing of MANETs.So more efficient power aware routing is required. The Enhanced Power awareMultipath Routing (EPMR) protocol efficiently utilizes the energy of nodes and resources .Thus increasesreliability and the lifetime of the network . The simulation tool used is NS2.Simulation results show that theenergy consumption of the network is less after applying EPMR protocol and shows better throughput andpacket delivery ratio